Analisis Faktor Leverage, Liquiditas, Profitabilitas, Ukuran Perusahaan, Kepemilikan Managerial dan Kepemilikan Institusional yang Mempengaruhi Voluntary Disclosure (Studi Empiris Pada Perusahaan Sektor Industri Dasar Dan Kimia, Aneka Industri dan I - Poni Hasperi; Sri Rahayu; Wiralestari (Jurnal Akuntansi & Keuangan Unja, 2020)
This study entitled is Analysis of Leverage, Liquidity, Profitability, Company Size, and Managerial Ownership and Institutional Ownership Factors that Influence Voluntary Disclosure (Empirical Studies in Basic and Chemical Industrial Companies, Miscellaneous Industries and Consumption Industries of Goods Listed on the Indonesia Stock Exchange for 2015-2018 period). This study tested 65 companies after purposive sampling. Significance test results show leverage, liquidity, profitability, company size, managerial ownership, and institutional ownership significantly influence voluntary disclosure. The results showed that leverage has no significant effect on voluntary disclosure, liquidity has no significant effect on voluntary disclosure, profitability has no significant effect on voluntary disclosure, firm size is not significant on voluntary disclosure, managerial investment has significant effect on voluntary disclosure, the institutional selection is significantly related to voluntary disclosure. Keywords: Voluntary Disclosure, Leverage, Liquidity, Profitability, Company Size, Managerial Ownership, Institutional Ownership